Ideological and artistic features of the novel "The End of the Legend" by A. Kekilbaev - Kabilov, Ә.Д.; Kamarova, Н.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines ideological and artistic features of Kekilbaev’s The End of the Legend. This work, which attracted attention with its innovation, revealed the hero's soul with great artistry, deeply immersing itself in his inner world. Using the example of the writer's work, the characteristics of the ‘intertwined style’ are considered, in which the author's narration and words, thoughts, and inner state of the hero's soul are intertwined in the writer's works, which was a novelty in our literature at the time. Influence of the existentialism movement, emphasizing various mysteries of humanity in the 20th-century philosophy, can be observed on ideological concept of the novel. The need to understand the unique essence of human life, to trace the inner world of a person by depicting his spiritual and emotional nature from a psychological point of view attracted the attention of readers. In modernist literature his world of feelings, the peculiarities of perception of events happening around him, the depiction of thoughts, impressions, and the state of the soul through the ‘stream of consciousness’ manifests itself in the poetic style of the writer. Ideological and artistic features of the novel are analyzed from the aspect of individual stylistic features of the author.